How is Health Promotion Research Undertaken in a Nordic Context? A Scoping Review of Doctoral Dissertations from 2008–2018 - Eriksson, Andrea; Andersen, Heidi Myglegård; Eriksson, Charli; Johannessen, Aud; Simonsen, Nina; Thualagant, Nicole; Torp, Steffen; Trollvik, Anne; Haglund, Bo J.A. (Socialmedicinsk tidskrift, 2020)
This scoping review was commenced as a collaboration within the Nordic Health Promotion Research Network (NHPRN). The overall aim was to explore how research under the label ‘health promotion’ was undertaken in a Nordic context. The search for dissertations published in Denmark, Finland, Iceland, Norway and Sweden was limited to the years 2008 to 2018. Manual searches of university websites, as well as different databases in the Nordic countries, were required for collecting dissertations from all universities. The collection of dissertations was more difficult than expected. There were 56 published PhD dissertations from 6 universities in Denmark, 51 from 8 universities in Finland, 0 from Iceland, 53 from 7 universities in Norway and 193 from 22 universities in Sweden. Almost half of the analysed dissertations combined qualitative and quantitative methods. About one-third of the dissertations had a settings approach, followed by a societal approach and individual approach. Finland and Sweden presented more intervention studies than the other countries. A majority of the intervention studies included individual lifestyle issues. Based on the analysis of the research approaches, more dissertations embracing societal perspectives and broader determinants of health may be recommended for future Nordic dissertations.